The Concept of Faith and the Ruling on the Major Sinner in Wa‘idiyyah Theology - Agha, Asma Alzroog (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
With this research, we would like to shed light on the issue of faith and the ruling of the perpetrator of the major sin in the thought of Al-Wa’idiyah, as an issue rooted in the life of the believer, and we aim to demonstrate the correct understanding of the texts of the Qur’an and Sunnah, to prove the correct belief, and to respond to the wrong innovated opinions and sayings. And the truth of the intellectual debate about the issue of faith and their position on the perpetrator of major sins, since this issue formed the most prominent hotbeds of the intense intellectual conflict that raged between Mu’tazili and Ash’ari thought, When the dispute occurred after the death of the Messenger, may God’s prayers and peace be upon him, the nation separated into several teams. Because of the difference in opinion, and he tried to direct all the thoughts of reaching the goal in the matter of faith and judging the salary of the major sin. And that is each according to the means of research and investigation available to him, so the response was with expressions filled with resentment, and its style was misleading and disparaging, but rather tafsiq, atonement and fraud, and they differed in the concept of faith, the texts of promise and intimidation, and the judgment of the perpetrators of major sins. Its members, and the dispute remained to this day, with (each doctrine reserved the privacy of its opinion), which led to a defect in the correct and established belief, and their understandings and ideas differed.